Virksomhedsleksikografi en viser tænder. Leksikografiske løsninger i København Zoo og Fagerberg A/S - Simonsen, Henrik Køhler (Nordiske Studier i Leksikografi, 2007)
This article discusses the challenge of satisfying the lexicographic and text genre-related demands of employees in two Danish companies. These employees not only have cognitive and communicative lexicographic demands but also a demand for text genre-related guidelines to be able to communicate eff ectively. This article addresses these challenges and proposes two theoretical models developed during two R&D projects in Copenhagen Zoo and Fagerberg A/S. The first model is the lexicographic convergence model, which facilitates convergence of the lexicographic dictionary article and integrated searches in eight external function-supporting sources. The second model is the lexicographic document template model, which facilitates the convergence of the lexicographic article and text genre data. The article finally demonstrates how the models were implemented in practice in the corporate dictionaries ZooLeks and FagerbergLex.